A Requirement Model of Web Based System for Tracking Student Attendance in Primary Schools (WB-TSA) - Dhunnis, Amrou Salem Ahmed (2009)
Web based system enables people to access digital information located in the Internet. The focus of this project is to apply Web based system development, particularly in observing students' attendance in primary school by instructors and parents of the students. The prospective system will facilitate the teachers to make attendance in a class and save it in the database of the school. By using the system, parents, teachers, administrator and head of school can easily monitor the attendance of their students during school hours. To achieve this goal, the study will adopt object oriented development life cycle as a methodology, the phases will be discussed in section of Research Methodology. Usability testing will be conducted to examine user's satisfaction. Lastly, the documentation that describes the detail of developed model is produced.